Protective effects of Panax notoginseng saponins on experimental myocardial injury induced by ischemia and reperfusion in rat - LI Xing; CHEN Jun-xiu; SUN Jia-jun (Acta Pharmacologica Sinica, 2016)
Effects of total saponins of Panax notoginseng (PNS) and purified ginsenosides Rb1 and Rg1 from PNS on myocardial injury induced by cardiac ischemia and reperfusion were studied with rat hearts in situ and in vitro. In pentobarbital-anesthetized rats, PNS pretreatment (100 and 200 mg/kg) provided significant reduction in myocardial infarct size after left descending coronary artery ligation (40 min) and reperfusion (120 min) in comparison with the control. PNS 12.5 and 25 mg/L, Rb1 10 mg/L, and Rg1 10 mg/L significantly decreased cardiac CPK release, attenuated myocardial Ca2+ accumulation, reduced malondialdehyde (MDA) production and prevented reduction of superoxide dismutase (SOD) activity in comparison with the control in perfused isolated rat hearts with global ischemia (40 min) and reperfusion (15 min). The results show that PNS, Rb1, and Rg1 prevent cardiac ischemia and the action is considered to be related to the inhibition of lipid peroxidation.